Analisis Perbandingan Sekuens Gen Calpain 1 (CAPN1) pada Sapi, Kerbau, dan Kambing Berdasarkan Database Genbank - Dody Houston Billhaq; Galy Hardyta; Labib Abdillah (LPPM Universitas Al Asyariah Mandar, 2023)
Livestock genetic improvement is the main purpose of animal breeding program. Biotechnology brings novel method to improve the animal breeding program qualitatively and quantitatively. Identification of gene sequence of polymorphism are used widely to analyze gene sequence to understand genetic variation. Calpain 1 (CAPN1) gene is the gene that involve in the process of improving meat quality such as marbling and tenderness of the livestock including the cattle, buffalo, and goat species. CAPN1 is responsible in encoding the µ-calpain that regulate postmortem proteolysis. This study collect the gene database including calpain 1 [Bos taurus (cattle)] NC_037356.1, calpain 1 [Bos indicus (zebu cattle)] NC_032678.1, calpain 1 [Bos indicus x Bos taurus (hybrid cattle)] NC_040104.1, calpain 1 [Bubalus bubalis (water buffalo)] NC_059161.1 calpain 1 [Capra hircus (goat)] NC_030836.1 through NCBI. Those collected gene were analyze using the Clustal W alignment, MEGA 11, and BLAST program. The results indicate that the cattle, buffalo, and goat species CAPN1 gene of the 5’ UTR, Intron, Exon, dan 3’ UTR region show 9 SNPs, 1691 SNPs, 153 SNPs, and 197 SNPs, respectively. Total of the identified SNPs within the the cattle, buffalo, and goat species CAPN1 gene comparison are 2050. This study can be used for the initial report in order to develop further research related to CAPN1 gene for the livestock ruminant.